PEMERIKSAAN KADAR GLUKOSA DARAH PUASA PADA PENDERITA DIABETES MELLITUS TIPE 2 BERDASARKAN AKTIVITAS FISIK - Eli Yusrita; Vina Juni Wulandari Ginting; Mega Elfia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Type 2 diabetes mellitus (DM) is a chronic metabolic disease characterized by increased glucose levels in the blood. Physical activity is one of the factors that can help control fasting blood glucose levels. This study aims to find out the description of fasting blood glucose levels in patients with type 2 Diabetes Mellitus based on physical activity. This study uses a quantitative descriptive design with a cross sectional approach. The results showed that 15 respondents (38.5%) had controlled fasting blood glucose levels (≤126 mg/dL), while 24 respondents (61.5%) had controlled blood glucose levels (126 mg/dL). The average fasting blood glucose level of all respondents was 173 mg/dL. Based on physical activity levels, 11 respondents (28.2%) had moderate physical activity (600-3000 METs) and 28 respondents (71.8%) had high physical activity (3000 METs). The conclusion of this study is that the majority of respondents have high physical activity, but blood glucose levels remain largely uncontrolled. This shows that physical activity alone is not enough to control blood glucose levels without thorough management such as diet, medical therapy, and other healthy lifestyles.Keywords: Type 2 Diabetes Mellitus, Fasting Blood Glucose, Physical Activity